The Influence of Self-Efficacy, Work Relations, and Career Development on Job Satisfaction with Organizational Climate as an Intervening Variable - Zul Irfan Harun; Yulasmi Yulasmi; Lusiana Lusiana (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the influence of self-efficacy, work relationships, and career development on organizational climate and job satisfaction in the Civil Service Police Unit and Fire Department of Pesisir Selatan Regency. The objects of this study are employees of the Civil Service Police Unit and Fire Department of Pesisir Selatan Regency, West Sumatra, Indonesia. The population in this study is 109 employees of the Civil Service Police Unit and Fire Department of Pesisir Selatan Regency. In this study, the sample was taken with a non-probability sampling design. The sample in this study was obtained by using saturated sampling, namely making the entire population into a sample of 109 people. Respondents in this study numbered 100 people. Data analysis used Structural Equation Modeling with the Partial Least Squares (SEM-PLS) approach. The results of the study indicate that self-efficacy, work relationships, and career development have a significant influence on organizational climate. Furthermore, self-efficacy, work relationships, and career development also have a significant influence on job satisfaction. However, organizational climate has a positive but insignificant influence on job satisfaction. A mediation test indicates that organizational climate does not mediate the relationship between self-efficacy, work relationships, and career development on job satisfaction. Meanwhile, work relationships have a significant influence on job satisfaction at the Civil Service Police Unit and the Pesisir Selatan Regency Fire Department. Career development has a significant influence on job satisfaction at the Civil Service Police Unit and the Pesisir Selatan Regency Fire Department.These findings confirm that self-efficacy, the quality of work relationships, and career development play a significant role in improving organizational climate and job satisfaction. However, organizational climate has not been able to act as a mediating variable in the relationship between individual factors and job satisfaction in this institutional context.